Cities, hinterlands and agglomeration shadows: spatial developments in Finland over 1880-2004 - Hannu Tervo (European Regional Science Association (ERSA), 2010)
This paper analyzes long-term spatial developments in Finland by focusing on two predictions of the new economic geography (NEG) models, the increasing persistence of locational patterns and the emerging agglomeration shadow, i.e. the rising dominance of growth centers. Pre- and post-war periods are distinguished to roughly express the shift from an agriculture-based economy to a post-industrial country. The analyses base on the assumption that each of the 19 Finnish regions has a center of its own and the rest of the region forms its local hinterland. The empirical analysis is based on regional population data from 1880 to 2004 at decade intervals. First, to analyze the persistence of locational patterns the variation in the rank of regions over time and the evolution in rank-size distributions at different stages of development are examined. Second, to analyze the dominance of centers and causal processes between cities and their local hinterland before and after WWII an extension of the Granger causality method using a panel framework is applied. The results indicated that persistence in locational patterns increased in Finland during the processes of industrialization and urbanization. Furthermore, in the pre-war period, centers and their hinterlands grew hand-in-hand, while the post-war period shows that cities cast an agglomeration shadow over their local hinterland. In all, the paper gives evidence in favour of the NEG predictions.
Keywords: 330; Regional development; Urbanization; Growth centers; Peripheral regions; New economicgeography; Rank-size rule; Granger causality; Finland